Peru-Brazil Relations. Recent Developments and Future Prospects - Acurio Traverso, Rómulo F. (2025)
This article reviews the current status, ongoing progress, and future prospects of relations between Peru and Brazil, considered from the perspectives of border integration and cooperation, economic and commercial relations, political and security dialogue, environmental sustainability, and sociocultural development, seeking to identify key elements of progress, obstacles, and promising prospects in each area.